Inactivation of the Prelimbic Cortex Impairs the Context-Induced Reinstatement of Ethanol Seeking - Palombo, Paola (Front Pharmacol, 2017)
Evidence indicates that drug relapse in humans is often provoked by exposure to the self-administered drug-associated context. An animal model called “ABA renewal procedure” has been used to study the context-induced relapse to drug seeking. Here, we reported a new and feasible training procedure for the ABA renewal method to explore the role of the prelimbic cortex in context-induced relapse to ethanol seeking. By using a saccharin fading technique, we trained rats to self-administer ethanol (10%). The drug delivery was paired with a discrete tone-light cue. Lever pressing was subsequently extinguished in a non-drug-associated context in the presence of the discrete cue. Rats were subsequently tested for reinstatement in contexts A or B, under extinction conditions. Ethanol-associated context induced the reinstatement of ethanol seeking and increased the expression of Fos in the prelimbic cortex. The rate of neural activation in the prelimbic cortex was 3.4% in the extinction context B and 7.7% in the drug-associated context A, as evidenced by double-labeling of Fos and the neuron-specific protein NeuN. The reversible inactivation of the neural activity in the prelimbic cortex with gamma-Aminobutyric acid (GABA) receptor agonists (muscimol + baclofen) attenuated the context-induced reinstatement of ethanol self-administration. These results demonstrated that the neuronal activation of the prelimbic cortex is involved in the context-induced reinstatement of ethanol seeking.